Therapeutic of Mesenchymal Stem Cells in Diabetes - Susanti Vinski, Deby; Cinta Vinski Borneo, Natasha (Journal of World Science, 2023)
This study aims to explain and analyze the effective treatment of diabetes mellitus by Mesenchymal Stem Cells with respect to traditional therapy based on oral anti-diabetic drugs. As well as to study its regularly consistent properties. The method used in this research is the case study method. Patient care records were the main source of data for this study including evaluation and analysis. So that the results of the study explain that at the same time the utilized products cultured by "CELLTECH STEM CELL LAB. and BANKING" as an integrated part of the Clinic, also get quality assurance. Effectiveness and efficiency including endogenous beta cell regeneration of pancreatic islets, and other therapeutic issues are novel and belong to cutting-edge treatment.  Treatments performed at the Vinski Regenerative Stem Cell Main Clinic have shown positive research results. This has strengthened the level of trust in the clinic's medical services.